2010
DOI: 10.1007/s00421-010-1603-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anti-saccade training with neck flexion on eye movement performance, presaccadic potentials and prefrontal hemodynamics in the elderly

Abstract: Anti-saccade performance, with strong contributions from frontal brain regions, reportedly deteriorates with age and maintenance of neck flexion and is known to cause brain activation. We investigated the effects of anti-saccade training on eye movement performance and frontal activity, and synergistic effects of training with neck flexion in the elderly. Thirty elderly individuals were divided into three equal groups: training group at neck resting position (NRT); training group at 20° neck flexion position (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…In previous studies, the shortening of saccadic reaction time associated with the neck flexion position was observed after the saccadic training with maintenance of neck flexion [3,20]. The present results could be effectively applied to older participants or be used in clinical investigations for patients with sensory perception impairments.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In previous studies, the shortening of saccadic reaction time associated with the neck flexion position was observed after the saccadic training with maintenance of neck flexion [3,20]. The present results could be effectively applied to older participants or be used in clinical investigations for patients with sensory perception impairments.…”
Section: Discussionsupporting
confidence: 62%
“…We previously reported that the significant shortening of saccadic reaction time associated with maintenance of neck flexion was observed in participants who belonged to a high-speed ball sports club; that is, a training effect of neck flexion on the brain activation existed [2,3,20]. In the preliminary experiment, we measured the saccadic reaction time during maintenance of neck flexion for 30 randomly selected healthy adults.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shortening of reaction time associated with maintaining neck flexion was also found in anti-saccade, in which gaze is oriented to a location situated at the same visual angle but in the opposite direction to an illuminated target [ 10 ], and this shortening was of a greater magnitude than that seen in pro-saccade [ 4 ]. Multiple cortical and subcortical regions are involved in anti-saccade, including the visual, parietal, prefrontal, and anterior cingulate cortices, frontal and supplementary eye fields, basal ganglia, cerebellum, thalamus, and superior colliculus [ 11 - 14 ].…”
Section: Introductionmentioning
confidence: 98%
“…Further, in the adaptation stage, the activated brain area during the task was larger in the elderly than in the young [21]. On the other hand, Kiyota and Fujiwara have reported that after anti-saccade training for 3 weeks, performance improved even for the elderly, and the peak amplitude of pre-saccadic brain potential increased, which is considered as an index of information processing and activation in the frontal brain regions [22]. These results suggest that even for the elderly, the frontal lobe function related to those tasks could be improved with repetitive training.…”
Section: Introductionmentioning
confidence: 99%